Terminology as a sensemaking social tool - Albuquerque, Alexandra (2015)
Since the middle of the first decade of this century, several authors have announced the dawn of a new Age, following the Information/ Knowledge Age (1970-2005?). We are certainly living in a Shift Age (Houle, 2007), but no standard designation has been broadly adopted so far, and others, such as Conceptual Age (Pink, 2005) or Social Age (Azua, 2009), are only some of the proposals to name current times. Due to the amount of information available nowadays, meaning making and understanding seem to be common features of this new age of change; change related to (i) how individuals and organizations engage with each other, to (ii) the way we deal with technology, to (iii) how we engage and communicate within communities to create meaning, i.e., also social networking-driven changes. The Web 2.0 and the social networks have strongly altered the way we learn, live, work and, of course, communicate. Within all the possible dimensions we could address this change, we chose to focus on language – a taken-for-granted communication tool, used, translated and recreated in personal and geographical variants, by the many users and authors of the social networks and other online communities and platforms. In this paper, we discuss how the Web 2.0, and specifically social networks, have contributed to changes in the communication process and, in bi- or multilingual environments, to the evolution and freeware use of the so called “international language”: English. Next, we discuss some of the impacts and challenges of this language diversity in international communication in the shift age of understanding and social networking, focusing on specialized networks. Then we point out some skills and strategies to avoid babelization and to build meaningful and effective content in mono or multilingual networks, through the use of common and shared concepts and designations in social network environments. For this purpose, we propose a social and collaborative approach to terminology management, as a shared, strategic and sense making tool for specialized communication in Web 2.0 environments.